SAPARDI DAN ARTIKULASI JERUK PURUT : SEBUAH PENDEKATAN CULTURAL STUDIES STUART HALL - Joko Santoso (CARAKA, 2014)
This work is aimed at concluding the process of jeruk purut articulation in Sapardi Djoko Damonoâ€™s short story: â€œDaun di Atas Pagarâ€. Articulation is Stuart Hallâ€™s theory in Cultural Studies which is conceiving cultural or structure as fragments of wholeness. It aimed to fuse two different elements or more and also investigating how ideology find it subject. Articulation means to utter, to forth also against myths while building it. The result is indicated in some cases. First, jeruk purut become an equal culture within autonomy with workers society of the modern city. Second, jeruk purut was no longer as a function only but fused with a meaning. Third, jeruk purut as a meaning have an equal level with the human.